Combining professionalization and personalization in English long-term care: analyzing stakeholder views through a workforce lens - Kispeter, Erika; Hussein, Shereen (Frontiers in Sociology, 2026)
IntroductionProfessionalizing the long-term care workforce, defined as improving the quality of care jobs, has been proposed as part of a solution to workforce challenges in long-term care. However, professionalization is argued to be in tension with personalization, a policy at the center of English long-term care. This article explores tensions and complementarities between the two policies through a workforce lens.MethodsWe conducted qualitative group (n = 2) and one-to-one interviews (n = 7) with long-term care stakeholders (n = 25) representing a wide range of organizations in England. We have adopted the method of thematic analysis to explore stakeholders' views on the relationship between the professionalization of the hands-on care workforce and the personalization of care and support services.ResultsWe have identified three points of intersection between professionalization and personalization in stakeholders' narratives: care workers' autonomy, training and registration. Autonomy is defined here as care workers' discretion to make practical decisions in a care situation without the immediate approval of a manager or care professional. We have found that narratives reflected a complex relationship between the two policies. Stakeholders viewed care workers' autonomy and training as directly supporting the goals of personalization but they perceived personal assistants' formal training and registration as being in tension with personalization.DiscussionCare workers' practical autonomy emerged from our analysis of stakeholder narratives as a key aspect of improving care jobs (professionalization). This supports research findings that a higher degree of autonomy improves job satisfaction and it is a source of dignity in an undervalued occupation. Yet, autonomy is not explicitly included in definitions of professionalization in the context of English long-term care. This article contributes to the literature by conceptualizing care workers' autonomy as a dimension of professionalization, along with pay, terms and conditions of employment, training and registration. Secondly, the results contribute to the literature and to policy debates about the relationship between professionalization and personalization, two mechanisms of reforming long-term care systems globally. Our results demonstrate that there is a complex relationship between the two policy areas, characterized by synergies and tensions.